Progression From Esophageal Thermal Asymptomatic Lesion to Perforation Complicating Atrial Fibrillation Ablation: A Single-Center Registry. (August 2017) - Halbfass, Philipp; Pavlov, Borche; Müller, Patrick; Nentwich, Karin; Sonne, Kai; Barth, Sebastian; Hamm, Karsten; Fochler, Franziska; Mügge, Andreas; Lüsebrink, Ulrich; Kuhn, Rainer; Deneke, Thomas
Abstract : Background—: Up to 40% of patients demonstrate endoscopically detected asymptomatic esophageal lesions (EDEL) after atrial fibrillation ablation. Methods and Results—: Patients undergoing first atrial fibrillation ablation and postinterventional esophageal endoscopy were included in the study. Occurrence of esophageal perforating complications during follow-up was related to documented EDEL (category 1: erythema/erosion; category 2: ulcer). In total, 1802 patients underwent first atrial fibrillation ablation procedure between January 2013 and August 2016 at our institution. Out of this group, 832 patients (506 male patients, 61%; 64.0±10.0 years) with symptomatic paroxysmal (n=345; 42%) or persistent atrial fibrillation underwent postprocedural esophageal endoscopy. Patients were ablated using single-tip ablation with conventional or surround flow irrigation and circular ablation catheters with open irrigation (nMARQ). In 295 of 832 patients (35%), a temperature probe was used. EDEL occurred in 150 patients (18%; n=98 category 1 EDEL, n=52 category 2 EDEL). In 5 of 832 patients (0.6%), an esophageal perforation (n=3) or an esophagopericardial or atrioesophageal fistula (n=2) occurred 15 to 28 days (19±6 days) after ablation. Two patients (1 atrioesophageal fistula and 1 esophagopericardial fistula) died. Esophageal perforation occurred only in patients with category 2 lesions (absolute risk, 9.6%). In a logistic regression analysis, ulcers were identified to be a significant predictor for esophageal perforating complications. Conclusions—: Postablation endoscopy seems to identify patients at high risk of esophageal perforating complications only occurring in patients with category 2 EDEL. One out of 10 postablation esophageal ulcers progressed to perforation, and no patient without esophageal thermal ulcers showed the occurrence of perforating esophageal complications.